2019
DOI: 10.1055/s-0039-3400285
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Injection of Botulinum Toxin A in Surgical Treatment of a Long Gap Esophageal Atresia—Rat Model

Abstract: Introduction Anastomosis with minimal tension is desirable in long-gap esophageal atresia. Prior studies in piglets showed that intraesophageal injection of botulinum toxin type A (BTX-A) results in significant esophageal elongation. Our aim was to determine the BTX-A dose, number of injections, and time necessary to elicit maximal response. Materials and Methods Adult male Wistar rats (n = 48) were randomly assorted into five groups. Four treatment groups received 2 or 4 U/kg of BTX-A, delivered usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…8 In the rat model, the elongation was higher after a waiting period of 24 hours compared with 6 hours confirming the time-related effect of BTX-A. 9 All studies were performed with the BTX-A injections on an in vivo exposed esophagus. As the peak in effect of BXT-A occurs between 1 and 3 weeks after administration, 10 11 preoperative administration seems more attractive.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…8 In the rat model, the elongation was higher after a waiting period of 24 hours compared with 6 hours confirming the time-related effect of BTX-A. 9 All studies were performed with the BTX-A injections on an in vivo exposed esophagus. As the peak in effect of BXT-A occurs between 1 and 3 weeks after administration, 10 11 preoperative administration seems more attractive.…”
Section: Introductionmentioning
confidence: 78%
“…6 7 8 9 This effect has been shown to be time dependent. 8 9 We were not able to recreate these results in this study, as we found no statistically significant difference between BTX-A and placebo when placing the injections endoscopically and with a 3-day waiting period. However, we were able to show a nonsignificant lower maximum load for the BTX-A group which is in line with the expected physiological effect of BTX-A.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, BTX-A inhibits the release of other neurotransmitters important for tonic muscular status, including adenosine triphosphate. Previous studies from our research group have shown that injections of BTX-A into the esophageal musculature in pigs and rats lead to a significant increase in esophageal elongation [ 18 19 ]. In addition, early evidence suggests a reduced stricture formation following esophageal anastomosis [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our research group have shown that injections of BTX-A into the esophageal musculature in pigs and rats lead to a significant increase in esophageal elongation [ 18 19 ]. In addition, early evidence suggests a reduced stricture formation following esophageal anastomosis [ 19 ]. We have also shown that administration of BTX-A via endoscopic techniques is feasible, and that the effect of BTX-A on esophageal elongation is dosage- and time-dependent [ 20 21 ].…”
Section: Introductionmentioning
confidence: 99%